The Bond Strength of Particulate-Filler Composite to Differently Oriented Fiber-Reinforced Composite Substrate - Lippo V.J. Lassila, DDS, MSc;1 Arzu Tezvergil, DDS, PhD;1 (Journal of Prosthodontics, 2007)
The primary failure mode of fiber-reinforced composite (FRC) materials used intraorally is delamination or debonding of particulate filler composite (PFC), the esthetic veneer, from the underlying FRC framework